The Influence Of Compensation And Work Discipline On Employee Performance: Case Study at PT Betawimas Cemerlang - Sari, Septia Ega; Tukirin, Tukirin (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Performance includes the work results obtained by an employee when completing tasks in accordance with the responsibilities given to achieve company goals. Factors that influence a person's performance will of course be influenced by employee compensation and discipline because income is in the form of money or goods, either directly or indirectly. indirect, which is received by employees as compensation for their services to the company. Meanwhile, the level of employee discipline also has an impact on the individual's performance. This research aims to understand the impact of compensation and work discipline on the performance of PT employees. Betawimas Brilliant. The research method uses a survey method where the population in this study is PT Betawimas Cemerlang employees, totaling 40 people. Data processing and analysis techniques use the SPSS program. The results of this research state that compensation does not have a significant effect on employee performance, but work discipline has a significant effect on employee performance, as well as simultaneously stating that the results have a significant effect